Behavioral Determinants of Open Defecation Free To Families in Soligi Village - Hairudin La Patilaiya; Sitti Nurhidayanti Ishak (CV. Inara, 2022)
Indiscriminate defecation (BABS) is an unhealthy behavior which is often encountered in everyday life. Until now, open defecation behavior in Soligi Village South Obi District is still being carried out. The purpose of this study was to analyze the determinants of open defecation free behavior in families in Soligi village. The type of research used is quantitative research with a cross sectional design. The sample was taken proportionally with a simple random sampling technique calculated using the Lemeshow formula with a proportion of 0.2 95% confidence level and 0.1 storage degree so that 135 families of samples could be found from a total population of 679 families, to avoid drop out samples plus 10% so that a sample of 145 families was obtained. Data analysis used univariate and bivariate with che-square test and p value < 0.05. The results of the study concluded that there was a significant relationship between knowledge, p-value = 0.001 less than = 0.05, attitude obtained p-value = 0.000 less than = 0.05, latrine ownership obtained p-value = 0.002 less than = 0.05, the availability of clean water obtained p-value = 0.000 less than = 0.05, the role of health workers obtained p-value = 0.000 less than = 0.05, and the role of community shops obtained p-value = 0.000 less than = 0.05 with open defecation behavior (BABS).